Materials analysis using a nuclear microprobe - Breese, Mark B. H. (John Wiley & Sons, 1996)
Three leading scientists combine their knowledge, gained over many years in two major microprobe facilities, to present an overview of the basic aspects of the technical requirements as well as detailed descriptions regarding the various uses of nuclear microprobes for materials analysis. Covers such topics as ion-solid interactions, crystallography and ion optics. Fully explains all the experimental factors associated with new analytical developments.